Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/inf2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sodium hydroxide for securing high thermoelectric performance in polycrystalline Sn1 − xSe via anisotropy and vacancy synergy

Abstract: The morphology and composition are two key factors to determine the thermoelectric performance of aqueously synthesized tin selenide (SnSe) crystals; however, their controlling is still under exploring. In this study, we report a high figure‐of‐merit (ZT) of ∼1.5 at 823 K in p‐type polycrystalline Sn1 − xSe resulted from a synergy of morphology control and vacancy optimization, realized by carefully tuning the sodium hydroxide (NaOH) concentration during solvothermal synthesis. After a comprehensive investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 63 publications
1
58
0
Order By: Relevance
“…Reproduced with permission. [170] Copyright 2019, Wiley. h) HRTEM image and inset SAED pattern of SnSe pellets viewed along the c-axis.…”
Section: Dopingmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [170] Copyright 2019, Wiley. h) HRTEM image and inset SAED pattern of SnSe pellets viewed along the c-axis.…”
Section: Dopingmentioning
confidence: 99%
“…However, solvothermal is a good choice to meet the goal of simultaneously improving the thermoelectric and mechanical properties. It was reported that at a strain rate of 2.5 × 10 −4 s −1 , competitive compressive strength of ≈52.1 and ≈77.0 MPa can be achieved along the ⊥ and // directions for solvothermally synthesized Sn 1− x Se ( x = 0.025),170 respectively, and both of which are very competitive with reported record value of 74.4 MPa achieved by a combustion method 95. This value is also comparable to the other commercial thermoelectric materials, such as PbTe and Bi 2 Te 3 312,313.…”
Section: Vacancy Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 26–30 ] High‐performance thermoelectric materials require high S , high σ, and low κ. [ 24,31–34 ] However, due to the strong coupling between these parameters, the optimization of thermal/electrical transport properties is the key for ZT enhancement. [ 35–40 ] The performance of thermoelectric materials can be enhanced from the two aspects: 1) optimization of electrical transportation performance and 2) minimization of thermal transport properties.…”
Section: Introductionmentioning
confidence: 99%